(untitled) - Cingelova, Gabriela (Civilia, 2016)
The article is based on research and the current state of contemporary history teaching in primary and secondary schools. The example of international (German-Czech-Polish project) shows how new media can be used in education, respectively in project teaching.
Keywords: Contemporary history; New media; Internet; German-Czech-Polish relations